Étude, protection et valorisation d’objets de la centrale de détention de l’abbaye de Fontevraud (Maine-et-Loire) - Clémentine Mathurin (In Situ)
Founded in 1101 by Robert d’Arbrissel, Fontevraud Abbey developed considerably in the Middle Ages and in the modern age. Converted into a central prison in 1804, the site underwent important transformations to adapt the premises for this new function. Following the closure of the central prison in 1963, a major program of works started which intended to restore the places to their past glory, the whole place having become a cultural site. In this dynamic of erasure, furniture and objects related to the prison were in their great majority destroyed or scattered. The progressive recognition of the importance of keeping traces of the long period of prison occupancy of the site however enabled to put in a safe place some 200 objects, often very modest but which bear important witness to the passage of hundreds of prisoners and guards within the walls of Fontevraud Abbey. The DRAC (Regional Department of Cultural Affairs) of the Pays de la Loire Region has carried out the procedure for historic monument protection, thereby granting this collection a heritage status worthy of its interest.